2 Ballinger's Annotated Codes and Statutes of Washington: Showing All Statutes in Force, Including the Session Laws of 1897, at 1957, § 7085 (1897) - (:unkn) unknown (My University, 1897)
That it shall be unlawful for any person, corporation or association of persons, or agents of any person, or member, agent or officer of any corporation or association of persons, to organize, maintain or employ an armed body of men in this state for any purpose whatever; and all parties so offending shall be deemed guilty of a misdemeanor
Keywords: MILITIAS